Análise da gestão de estoque de um estabelecimento comercial do ramo de moto peças da cidade de São Paulo do Potengi/RN - Freire, Denyeivisson da Silva (Universidade Federal Rural do Semi-Árido, 2019)
Inventory management is a very relevant area to look into within an organization, which is necessary due to inventory products that are idle for long periods and have a high chance of becoming superfluous, retaining much of the organization's capital investment. This work aimed to perform the inventory sector analysis of a motorcycle parts business establishment, located in the city of São Paulo do Potengi in Rio Grande do Norte. For this, the inventory of the parts was surveyed, to make groups that will be classified according to their importance, using the ABC curve tool. The study was conducted from May to July 2019, where there was contact with the manager of the company and subsequent technical visits to it. Data collection was done through the SIC software used in the company. The products were divided into five groups according to the characteristics of the elements and the ABC curve was performed for each group. Within the inventory control study, tools such as safety stock and replenishment point were used. We used the safety stock and the point of replenishment, the calculation for the purchase of the lubricating oil product, because according to the manager owns most of the company's sales. For this item, the safety stock was 12 units of the product and the re-supply point with 21 units. With the end of this work, it can be observed that actually a smaller volume of inventory is responsible for most of the company's revenues.
Monografia
Keywords: Gestão de estoque; Curva ABC; Estoque de segurança; Stock management; ABC curve; Safety stock; ENGENHARIAS::ENGENHARIA DE PRODUCAO